2020
DOI: 10.1039/d0em00262c
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation and the toxicity mechanism of synergism within three organophosphorus pesticide mixtures to Chlorella pyrenoidosa

Abstract: Organophosphorus pesticide (OPP) pollutants in the environment are of toxicity risks to the living organisms, and the possible toxicity mechanism needs to be further clarified. Therefore, individual and combined toxicity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It had been shown that the toxicity of mixtures of organophosphorus pesticides (OPPs) to Chlorella proteolytica was linearly related to the p i . 60 Hence, to unveil the pivotal components contributing to the mixture's toxicity, we conducted Pearson correlation analyses and scrutinized the toxicity of each exposure time in relation to the p i . And the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It had been shown that the toxicity of mixtures of organophosphorus pesticides (OPPs) to Chlorella proteolytica was linearly related to the p i . 60 Hence, to unveil the pivotal components contributing to the mixture's toxicity, we conducted Pearson correlation analyses and scrutinized the toxicity of each exposure time in relation to the p i . And the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Synergistic reactions of chemical combinations can produce severe negative impacts on the animal population, threatening the regular function of the water ecosystem 33 . To identify the possible synergistic reactions among chemicals, the toxic mechanism of chemical combinations should be clarified 34 . In the current work, the combination of chlorpyrifos and bifenthrin was included in one three-component mixture (Cd-chlorpyrifos-bifenthrin), three four-component mixtures (Cd-acetamiprid-chlorpyrifos-bifenthrin, Cd-carbendazim-chlorpyrifos-bifenthrin, and Cd-azoxystrobin-chlorpyrifos-bifenthrin), three five-component mixtures (Cd-acetamiprid-carbendazim-chlorpyrifos-bifenthrin, Cd-acetamiprid-azoxystrobin-chlorpyrifos-bifenthrin, and Cd-carbendazim-azoxystrobin-chlorpyrifos-bifenthrin), and one six-component mixture (Cd-acetamiprid-carbendazim-azoxystrobin-chlorpyrifos-bifenthrin), and all these mixtures exerted synergistic responses on D. rerio under two types of testing situations.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality data at different concentrations were obtained through experiments. The Weibull two-parameter (location α and shape β) nonlinear fitting function 48 , 49 was used to fit the concentration effect data. The Weibull function expression is shown as follows where f ( x ) is the lethality to C. elegans and x is the concentration of a single component or a mixture ray.…”
Section: Methodsmentioning
confidence: 99%